2020
DOI: 10.1016/j.ccell.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

ADORA1 Inhibition Promotes Tumor Immune Evasion by Regulating the ATF3-PD-L1 Axis

Abstract: Highlights d ADORA1 inhibition promotes immune escape by regulating tumor PD-L1 via ATF3 d ADORA1 or ATF3 screening may be used to assess PD-1 mAb therapy efficacy d Combination of an ADORA1 antagonist and a PD-1 mAb provides therapeutic benefit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 41 publications
15
104
1
Order By: Relevance
“…Unlike adenosine receptor A2AR, A2BR, and A3, one study showed adenosine receptor A1 (ADORA1) signaling axis suppresses tumor PD-L1-mediated immune evasion (94). Downregulation and inhibition of adenosine receptor A1 (ADORA1) significantly induces tumor PD-L1 expression by promoting ATF3 transcriptional activity.…”
Section: Tumor Metabolites Promote Tumor Immune Evasion Adenosinementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike adenosine receptor A2AR, A2BR, and A3, one study showed adenosine receptor A1 (ADORA1) signaling axis suppresses tumor PD-L1-mediated immune evasion (94). Downregulation and inhibition of adenosine receptor A1 (ADORA1) significantly induces tumor PD-L1 expression by promoting ATF3 transcriptional activity.…”
Section: Tumor Metabolites Promote Tumor Immune Evasion Adenosinementioning
confidence: 99%
“…Downregulation and inhibition of adenosine receptor A1 (ADORA1) significantly induces tumor PD-L1 expression by promoting ATF3 transcriptional activity. Although the role of adenosine signaling in tumor immunity is different from that in immune cells, the antagonist of the adenosine receptor 8-cyclopentyl-1,3-dipropylxanthine (DPCPX) has demonstrated synergistic effect with PD-1 antibody in melanoma and non-small cell lung cancer (NSCLC) ( 94 ).…”
Section: Tumor Metabolites Promote Tumor Immune Evasionmentioning
confidence: 99%
“…In addition, altered Ca 2+ influences Ca 2+ /cyclic AMP (cAMP) signaling pathway contributing to the regulation of cytokines [ 35 ]. Both the excretion of cytokines and change in cAMP pathway are associated with tumor progression [ 12 , 36 ]. These findings could be the potential mechanism of DCK regulating the expression of inhibitor receptors and contributing to the progression of a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that A1R deletion suppressed melanoma-derived cell growth and induced the inhibition of T cells in co-culture, antagonizing the anti-tumor immune response depending on another A2AR receptor, through a pathway involving overexpression of PD-L1 driven by the transcription factor ATF3 [144]. Taken together, these observations lead us to conclude that actions of ARs are too complex and could be opposite in diverse physiological events.…”
Section: Purines and Evasion Of Immune Attackmentioning
confidence: 91%